Pengaruh Fungsional Peralatan Keamanan terhadap Kinerja Petugas Unit Aviation Security di Bandar Udara Internasional Adi Soemarmo Boyolali - Putri, Shelly Nabila; Awan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to determine the effect of Functional Security Equipment on the Performance of Aviation Security Unit Officers at Adi Soemarmo Boyolali International Airport to be able to improve the performance of human resources in order to realize flight security and safety. This research was conducted at Adi Soemarmo Boyolali International Airport from 05 December 2022 to 05 January 2023. The data collection method used in this study was a quantitative method. The population in this study were all Aviation Security unit officers at Adi Soemarmo Boyolali International Airport, totaling 80 respondents and the sampling technique used in this study was Simple Random Sampling and the analytical tool used in this study was simple linear regression. The results of the regression test show that the functional variable of security equipment has a positive effect on the performance of aviation security unit officers and the results of hypothesis testing indicate that the functional variable of security equipment has a significant effect on the performance of aviation security unit officers. The results of the determination test produce an adjusted R square value in the regression model obtained at 0.766. This indicates that 76.6% of the variation in the magnitude of the variation in performance variable changes can be explained by the functional variable of safety equipment and the results of the partial test show a significance level of 0.000 <0.05. This proves that the functional security equipment has an effect on performance. Keywords : functional security equipment, performance.